Safety-factor dataset for high embankments determined with different analytical methods - Mesa Lavista, Milena; Alvarez Pérez, José; Tejeda Piusseaut, Eduardo; Lamas Fernández, Francisco (Elsevier, 2021)
Slope-stability analysis is one of the parameters in the design of road embankments that the designer must consider in order to ensure stable and safe construction. The technical standards recommend slopes to heights of 12 m, depending on the soil types and the topography. In the present work, the limit equilibrium methods (Fellenius, Bishop, Janbu, Morgensten-Price) and the finite element method are used to determine the safety factor of road embankments for different slopes flanking the road. Five embankment heights were simulated: 6 m, 12 m, 18 m, 24 m, and 30 m. The dataset compiled can be used for modeling embankments.